Fiscal Decentralization and Corruption: The Facts of Regional Autonomy Policies in Indonesia - Ahmad Syarif (JSP (Jurnal Ilmu Sosial dan ilmu Poltik), 2023)
Decentralization has posed new problems in Indonesian local governments, including disparities between regions, poor public services, fiscal indiscipline, and corruption cases. Before the implementation of regional autonomy, corruption cases were reported only in a few regions. A year after decentralization started, in 2002, more corruption cases were reported in more regions nationwide. The irony is that such decentralization, initiated to reduce corruption in the government, ended up with more corruption in the regions. This study investigates the relationship between fiscal decentralization—as proxied by capital expenditure and fiscal independence index—and the corruption index. This study also analyzes the macro factors and regional characteristics: inflation, civil servants’ salaries, education levels, and the differences in the corruption index at the regional level. The method used in this study is regression analysis by using panel data from longitudinal studies involving 15 cities in Indonesia in 2008, 2010, 2015, and 2017. The finding shows that the relationship of fiscal decentralization—expenditure, inflation rates, civil servants’ salaries, and local corruption—are not statistically significant to the corruption index. By contrast, the relationship between the fiscal independence index and educational level are statistically significant. The implementation of fiscal decentralization on expenditure increases corruption risks due to ineffective budget management, individual corrupt tendencies, and weak supervision system. Meanwhile, fair allocation of local income can increase public trust and prosperity and lower corruption risks.